Advancements in Liposomal Nanomedicines: Innovative Formulations, Therapeutic Applications, and Future Directions in Precision Medicine - Izadiyan Z; Misran M; Kalantari K; Webster TJ; Kia P; Basrowi NA; Rasouli E; Shameli K (International Journal of Nanomedicine)
Zahra Izadiyan,1 Misni Misran,1 Katayoon Kalantari,2 Thomas J Webster,3,4 Pooneh Kia,5 Noor Ashyfiyah Basrowi,1 Elisa Rasouli,6 Kamyar Shameli7 1Department of Chemistry, Universiti Malaya, Kuala Lumpur, Malaysia; 2Department of Chemical Engineering, Northeastern University, Boston, MA, USA; 3Biomedical Engineering, Hebei University of Technology, Tianjin, People’s Republic of China; 4School of Engineering, Saveetha University, Chennai, India; 5Institute of Bioscience, Universiti Putra Malaysia, Serdang, Selangor, Malaysia; 6Department of Electrical and Electronics Engineering, Nanyang Technological University, Nanyang, Singapore; 7School of Medicine, Institute of Virology, Technical University of Munich, Munich, GermanyCorrespondence: Zahra Izadiyan; Kamyar Shameli, Email zahra_izadiyan@yahoo.com.my; kamyarshameli@gmail.comAbstract: Liposomal nanomedicines have emerged as a pivotal approach for the treatment of various diseases, notably cancer and infectious diseases. This manuscript provides an in-depth review of recent advancements in liposomal formulations, highlighting their composition, targeted delivery strategies, and mechanisms of action. We explore the evolution of liposomal products currently in clinical trials, emphasizing their potential in addressing diverse medical challenges. The integration of immunotherapeutic agents within liposomes marks a paradigm shift, enabling the design of ‘immuno-modulatory hubs’ capable of orchestrating precise immune responses while facilitating theranostic applications. The recent COVID-19 pandemic has accelerated research in liposomal-based vaccines and antiviral therapies, underscoring the need for improved delivery mechanisms to overcome challenges like rapid clearance and organ toxicity. Furthermore, we discuss the potential of “smart” liposomes, which can respond to specific disease microenvironments, enhancing treatment efficacy and precision. The integration of artificial intelligence and machine learning in optimizing liposomal designs promises to revolutionize personalized medicine, paving the way for innovative strategies in disease detection and therapeutic interventions. This comprehensive review underscores the significance of ongoing research in liposomal technologies, with implications for future clinical applications and enhanced patient outcomes.Keywords: liposomes, active targeting, targeted drug delivery, nano-carriers, cancer therapy